Carbonate buffer mixture and fecal microbiota transplantation hold promising therapeutic effects on oligofructose-induced diarrhea in horses - Tuniyazi, Maimaiti; Tang, Ruibo; Hu, Xiaoyu; Fu, Yunhe; Zhang, Naisheng (Frontiers in Veterinary Science, 2024)
Diarrhea is a common gastrointestinal disorder in horses, with diet-induced diarrhea being an emerging challenge. This study aimed to investigate the gut microbiota differences in healthy and diet-induced diarrheic horses and evaluate the effectiveness of fecal microbiota transplantation (FMT) and Carbonate Buffer Mixture (CBM) as potential therapeutic approaches. Twenty healthy horses were included in the study, with four groups: Control, Diarrhea, CBM, and FMT. Diarrhea was induced using oligofructose, and fecal samples were collected for microbiota analysis. FMT and CBM treatments were administered orally using donor fecal matter, and formula mixture, respectively. Clinical parameters, serum levels, intestinal tissue histopathology, and fecal microbiota profiles were evaluated. The results showed that diarrhea induction disbalanced the gut microbiota with decreased diversity and richness, affected clinical parameters including elevated body temperature and diarrhea score, and decreased fecal pH, increased inflammatory responses such as increased serum LPS, IL-17A, lactic acid and total protein, and caused damage in the colon tissue.CBM and FMT treatments altered the gut microbiota composition, restoring it towards a healthier profile compared to diarrheic, restored the gut microbiota composition to healthier states, improved clinical symptoms including decreased body temperature and diarrhea score, and increased fecal pH, decreased inflammatory responses such as increased serum LPS, IL-17A, lactic acid and total protein, and repaired tissue damage. CBM and FMT Spearman correlation analysis identified specific bacterial taxa associated with host parameters and inflammation. FMT and CBM treatments showed promising therapeutic effects in managing oligofructoseinduced diarrhea in horses. The findings provide valuable insights into the management and treatment of diarrhea in horses and suggest the potential of combined CBM and FMT approaches for optimal therapeutic outcomes.